2001
DOI: 10.1053/jhep.2001.26520
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of silymarin on estrogen-induced cholestasis in the rat: A study in vivo and in isolated hepatocyte couplets

Abstract: The effect of silymarin (SIL) on 17␣-ethynylestradiol (EE)-induced cholestasis was evaluated in rats. EE (5 mg/kg, subcutaneously, daily, for 5 days) decreased both the bilesalt-dependent and the bile-salt-independent fractions of the bile flow. The decrease in the former was associated to a reduction in the bile salt pool size (؊58%), and this effect was completely prevented by SIL. This compound also counteracted the inhibitory effect induced by EE on HCO 3 ؊ but not glutathione output, 2 major determinants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
52
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 63 publications
14
52
0
1
Order By: Relevance
“…Similarly, silymarin was found to retard collagen accumulation associated with both early and advanced biliary fibrosis in experimental model of complete bile duct occlusion induced by Ethibloc in rats (Luper, 1998). In experimental model of choleostasis induced by 17α-ethynylestradiol (EE) in rats, silymarin exerted protective effects by normalizing the EE-induced decrease in bile salt pool size and HCO 3 − , and by counteracting cholestatic effect of its glucuronidated metabolite (Crocenzi et al, 2001). In yet another study conducted by the same group, hepatoprotective effects of silymarin were observed in monohydroxylated bile salt (BS) taurolithocholate (TLC)-induced choleostatsis in rats by preventing the impairment of both BS-dependent and -independent fractions of the bile flow (Crocenzi et al, 2003).…”
Section: Milk Thistle Extract Silymarin and Silibinin: Pharmacology mentioning
confidence: 99%
“…Similarly, silymarin was found to retard collagen accumulation associated with both early and advanced biliary fibrosis in experimental model of complete bile duct occlusion induced by Ethibloc in rats (Luper, 1998). In experimental model of choleostasis induced by 17α-ethynylestradiol (EE) in rats, silymarin exerted protective effects by normalizing the EE-induced decrease in bile salt pool size and HCO 3 − , and by counteracting cholestatic effect of its glucuronidated metabolite (Crocenzi et al, 2001). In yet another study conducted by the same group, hepatoprotective effects of silymarin were observed in monohydroxylated bile salt (BS) taurolithocholate (TLC)-induced choleostatsis in rats by preventing the impairment of both BS-dependent and -independent fractions of the bile flow (Crocenzi et al, 2003).…”
Section: Milk Thistle Extract Silymarin and Silibinin: Pharmacology mentioning
confidence: 99%
“…Although being used in clinical practice worldwide, its therapeutic efficacy has been questioned for years. Potent scavenging properties have been demonstrated in vitro and in vivo, in different hepatic and non-hepatic cells [18,19]; and strong evidences for silibinin therapeutic efficacy have been reported in different types of experimental liver injury [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…EE-treated rats were administered EE dissolved in propylene glycol (33.7 mM), at a daily dose of 5 mg/kg b.wt. s.c. for 5 consecutive days (Crocenzi et al, 2001). Control rats received injections of vehicle (propylene glycol; 0.5 ml/kg b.wt.…”
Section: Methodsmentioning
confidence: 99%
“…Estrogens contribute to the pathogenesis of both oral contraceptive-induced cholestasis and cholestasis of pregnancy (Vore, 1987;Reyes and Simon, 1993). Ethynylestradiol (EE), a synthetic estrogen, decreases bile flow formation in experimental animals, thus representing a useful model to study both estrogen-and drug-induced cholestasis (Crocenzi et al, 2001). In the rat, EE-induced decreases in both bile salt-dependent and -independent bile flow are attributed to decreased expression and activity of the canalicular bile salt export pump (Abcb11) and Mrp2 (Trauner et al, 1997;Lee et al, 2000) and concomitant impairment in biliary excretion of bile salts and Mrp2 substrates, such as glutathione species.…”
mentioning
confidence: 99%